Retrospective analysis of cardiac index and lactate production on cardiopulmonary bypass for a congenital cardiac patient population. (April 2019) - Clingan, Sean; Reagor, James; Lombardi, John
Background: Providing adequate metabolic support is the principal concern during cardiopulmonary bypass (CPB) with different strategies utilized to enhance oxygen delivery to the patient. Modifying temperature, hematocrit (Hct) and cardiac index (CI) during CPB are primary techniques which aid in this effort. Based upon surgeon preference, the study institution employs differing perfusion strategies (PS) during congenital cardiac surgery requiring CPB. One method utilizes a 2.4 L/min/m 2 CI and nadir Hct of 28% (PS1) and the other a 3.0 L/min/m 2 CI with a nadir Hct of 25% (PS2). Methods: Cardiopulmonary bypass cases during which the PS1 or PS2 strategies were applied were retrospectively examined, finding no significant difference in pre-CPB lactate, maximum lactate on CPB or maximum change in lactate on CPB. Results: While the post-CPB lactate was statistically significantly higher in the PS2 group (p=0.024), the magnitude of difference (0.15 mmol/L) was small. Conclusions: This study illustrates that, when oxygen delivery or tissue perfusion is suspected as the primary cause of lactate production during CPB, increasing the CI to a 3.0 rather than a 2.4 CI may be more advantageous than packed red blood cell administration.